Stylized facts from prices at multi-channel retailers in Mexico - Diego Solórzano (Banco de México, 2023)
Using data gathered through web scraping techniques, this paper characterizes product categories' frequency, size and dispersion of price changes in eight retail chains in Mexico, and compare them with price statistics stemming from brick and mortar stores data of the same retailers. Notably, between 2016 and 2019, prices observed in brick and mortar stores (offline) change more frequently than those observed on websites (online). However, given a price change, online prices tend to exhibit larger price changes than their offline counterparts. In 2020, period affected by the pandemic, the above relationship across sales channel holds, while the frequency of price changes increased roughly by the same magnitude in both sales channels and the average size of price adjustments did not change relative to previous years. Results from this paper highlight the importance of recognizing the differences between survey and web scraped data.
Keywords: E31; L16; 330; Nominal rigidities; Consumer prices; Web scraped data; Survey microdata